1986
DOI: 10.1128/aac.30.5.785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calmodulin inhibitors on viability and mitochondrial potential of Plasmodium falciparum in culture

Abstract: mmol) (both from New England Nuclear Corp.). Parasites were harvested, and radioactivity was determined as previously described (11,17).Epifluorescence microscopy was used to monitor rhodamine 123 (RH123) retention in parasite mitochondria as previously described (12) Fig. 1 RH123 concentrated in the parasite mitochondrion (Fig. 2A); 5 juM CM eliminated this fluorescence within 5 min (Fig. 2B). Similar results were observed with 32 jiM CPZ and 10 jiM TFP. These concentrations did not affect the faint cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…Previous studies have demonstrated that alterations of the erythrocyte membrane such as cross-linking of spectrin, changes in deformability, spherocytosis, and modification of the cytoskeletal proteins have inhibitory effects on invasion (8,11,20,21). To our knowledge, no studies of incorporation of lupeol into erythrocytes and its effect on parasite proliferation have been reported prior to this work.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies have demonstrated that alterations of the erythrocyte membrane such as cross-linking of spectrin, changes in deformability, spherocytosis, and modification of the cytoskeletal proteins have inhibitory effects on invasion (8,11,20,21). To our knowledge, no studies of incorporation of lupeol into erythrocytes and its effect on parasite proliferation have been reported prior to this work.…”
Section: Discussionmentioning
confidence: 65%
“…A modification of Desjardins' radioisotope method (6) for measuring the growth of a chloroquine-sensitive strain of P. falciparum (3D7) was adopted, with incorporation of [ 3 H]phenylalanine as an index of growth (11). Thus, 50 l of the growth medium (RPMI 1640 with HEPES and supplemented with 0.45% Albumax II, 1.42 mM L-glutamine, 133 M hypoxanthine, and 44 mg of gentamicin sulfate/ml) containing test substances added from a dimethyl sulfoxide (DMSO) stock (lupeol) or a water stock (amphiphiles) was mixed with 50 l of a suspension of parasitized erythrocytes (blood type, O; hematocrit, 5%; parasitemia, 2 to 3%) in 96-well microtiter plates.…”
Section: Methodsmentioning
confidence: 99%
“…2). Most (71%) of the mice treated with chloroquine alone died before day 10. Given alone, both racemate and (+)-amlodipine, were totally inactive at doses of 30 or 40 mg/kg daily.…”
Section: Methodsmentioning
confidence: 99%
“…At the protein level, contradictory observations on the presence or absence of a P glycoprotein-like structure in malaria parasites were reported (14,38). Both calcium channel blockers and calmodulin inhibitors inhibit, in voltage-independent and calmodulin-independent manners, numerous enzymes present in malaria parasites (10,16,28). Some of these enzymes may be involved in the transport of chloroquine into malaria parasites (11,33).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work Wasserman et al (1982) showed that in the presence of EGTA the young trophozoites developed only for a few hours and then the cycle was irreversibly arrested. In other studies (Geary et al 1986, Matsumoto et al 1987, Tanabe et al 1989) it has been reported that calmodulin antagonists and calcium blockers inhibit the growth of P. falciparum in red cells. Elsewhere we have reported an entrance of calcium in the erythrocyte during invasion ).…”
mentioning
confidence: 99%